Betrixaban: Impact on Routine and Specific Coagulation Assays—A Practical Laboratory Guide - Siriez, Romain; Evrard, Jonathan; Dogné, Jean-Michel; Pochet, Lionel; Gheldof, Damien; Chatelain, Bernard; Mullier, François; Douxfils, Jonathan (Thrombosis and Haemostasis, 2018)
Introduction Betrixaban is a novel direct oral factor Xa inhibitor approved by the Food and Drug Administration for prophylaxis of venous thromboembolism in adult patients hospitalized for an acute illness at risk for thromboembolic complications. Assessment of the anti-coagulant effect of betrixaban may be useful in some situations. Also, clinicians need to know how routine coagulation assays are influenced.Objective The aim of this study is to determine which coagulation assay(s) should be used to assess the impact of betrixaban on haemostasis and provide laboratory guidance for their interpretation.Materials and Methods Betrixaban was spiked at final concentrations ranging from 0 to 250 ng/mL in platelet-poor plasma. Different reagents from several manufacturers were tested and the impact of betrixaban on pro-thrombin time (PT), activated partial thromboplastin time (aPTT), dilute Russel viper venom time (dRVV-T), chromogenic anti-Xa assays, thrombin generation assay (TGA), and a large panel of haemostasis diagnostic tests has been assessed.Results A concentration-dependent prolongation of aPTT, PT and dRVV-T is observed. The sensitivity mainly depends on the reagent. Chromogenic anti-Xa assays show high sensitivity depending on the reagent and/or the methodology. These assays applicable for other direct factor Xa inhibitors have to be adapted to obtain a relevant range of measurement. TGA may also be attractive to assess the anti-coagulant activity of betrixaban.Conclusion Adapted chromogenic anti-Xa assays are the most appropriate assays to estimate the concentration of betrixaban. Betrixaban significantly affects several haemostasis diagnostic tests and this needs to be taken into consideration when requesting and interpreting such tests.
Keywords: betrixaban; drug measurement; coagulation tests; guidance; factor Xa inhibitors